2010
DOI: 10.1038/jid.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Autophagy and Inhibition of Melanoma Growth In Vitro and In Vivo by Hyperactivation of Oncogenic BRAF

Abstract: Activating mutations in NRAS and BRAF are found frequently in cutaneous melanomas. Because concurrent mutations of both BRAF and RAS are extremely rare, it is thought that transformation by RAS and BRAF occurs through a common mechanism. Also, there is evidence for a relationship of synthetic lethality between NRAS and BRAF oncogenes that leads to selection against cells with a hyperactive mitogen-activated protein kinase (MAPK) pathway. However, it is not known whether the hyperactivation of the MAPK pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 44 publications
5
55
0
2
Order By: Relevance
“…These findings indicate that autophagy enables Ras-induced oncogenesis by maintaining functional mitochondria and oxidative metabolism. The importance of the Ras/ Raf/MEK/ERK cascade in the regulation of autophagy is further corroborated by the finding that hyperactivation of oncogenic BRAF induces autophagy whereas specific inhibition on MEK or depletion of ERK inhibits autophagy Maddodi et al, 2010).…”
Section: V12mentioning
confidence: 53%
“…These findings indicate that autophagy enables Ras-induced oncogenesis by maintaining functional mitochondria and oxidative metabolism. The importance of the Ras/ Raf/MEK/ERK cascade in the regulation of autophagy is further corroborated by the finding that hyperactivation of oncogenic BRAF induces autophagy whereas specific inhibition on MEK or depletion of ERK inhibits autophagy Maddodi et al, 2010).…”
Section: V12mentioning
confidence: 53%
“…In particular, we and others have recently demonstrated that melanomas harbouring mutant BRAF V600E display an increased basal autophagic rate. 3,20,30,31 In order to confirm this observation, we compared basal autophagic flux in melanoma cell lines, CHL-1 and A375, with BRAF wild-type (wt) or V600E-mutated alleles, respectively. As shown in Figure 1a, A375 cells displayed increased expression of lipidated LC3 compared with CHL-1 cells, which was sustained by co-treatment with bafilomycin A (Baf), to prevent autophagic flux.…”
Section: Resultsmentioning
confidence: 95%
“…Although the small numbers and unmatched sample groups are inevitable in our study, Fisher's exact tests revealed that there was a significant association between expression of LC-3 and Pin1 (p Ͻ 0.010). Recently, quantitative immunohistochemical analysis of human melanomas showed a strong correlation between the levels of B-Raf protein and LC-3, suggesting that high oncogenic B-Raf levels trigger autophagy, which may have a role in tumor progression (19). In the context of B-Raf signaling, the oncogenic activity of B-Raf was increased in cells overexpressing wild-type Pin1, whereas their transforming activity was reduced in cells overexpressing a dominant negative Pin1 (20).…”
Section: Discussionmentioning
confidence: 99%